Pengembangan Aplikasi Manajemen Proyek Berbasis Android Menggunakan Metode Incremental pada PT Bahtera Pintas Utama - Mohamad Zainudin; Mochamad Adhari Adiguna (PT Triputra Sejahtera Prima, 2024)
In managing projects, the role of technology and information is crucial for PT Bahtera Pintas Utama, a contractor specializing in the procurement of goods and services in the field of fiber optics. However, the current practice involves using the WhatsApp platform to support project management, which is not recommended due to its nature as a social media platform, not a structured project management tool. Additionally, there are risks of data leakage, loss, and difficulties in managing sent documentation. The company requires a structured and easily accessible system from anywhere, making a mobile application an appropriate choice, especially with the popular Android operating system. With this system, project management becomes more streamlined, reducing errors and documentation deficiencies, and facilitating project progress monitoring. The research employs observation and interview methods, while the application development follows an incremental approach. As a result, project management becomes more efficient and structured. Quick access from smartphones eases monitoring and minimizes documentation errors. This system aids the company's management in monitoring and overseeing projects with up-to-date information, systematically organized from project acceptance to progress monitoring. The development utilizes Laravel framework as the backend, Flutter framework as the frontend, and RESTful API in its integration.